Private School Participation in Pakistan - Nguyen, Quynh; Raju, Dhushyanth (World Bank, Washington, DC, 2014)
Private schooling is an important feature of the educational landscape in Pakistan and is increasingly a topic of public and government discourse. This study uses multiple rounds of national household sample surveys to examine the extent and nature of private school participation at the primary and secondary levels in Pakistan. Today, one-fifth of children -- or one-third of all students -- go to private school in Pakistan. Private school students tend to come from urban, wealthier, and more educated households than do government school students and especially out-of-school children. Important differences exist across Pakistan s four provinces with respect to the characteristics of private school students relative to government school students, as well as in the composition of private school students. Private schooling is highly concentrated, with a few districts (situated mainly in northern Punjab province) accounting for most of the private school students. Private school participation among children varies largely from one household to another, rather than within households, and to a greater extent than does government school participation. The spatial patterns of private school supply are often strongly correlated with the spatial patterns of private school participation. In the 2000s, private school participation rates grew in Punjab, Sindh, and Khyber Pakhtunkhwa provinces and across socioeconomic subgroups, contributing in particular to the growth in overall school participation rates for boys, children from urban households, and children from households in the highest wealth quintile. Nevertheless, the composition of private school students has become less unequal over time. This trend has been driven mainly by Punjab province, which has seen declines in the shares of private school students from urban households and households in the highest wealth quintile.